EVENT MANAGEMENT AS AN EFFECTIVE TOOL OF ENSURING COMMUNICATION STRATEGY IN PUBLIC ADMINISTRATION - ЛАРІНА, Наталія; ЛАРІН, Станіслав; ІВАНИЦЬКИЙ, Назар (Київський національний університет імені Тараса Шевченка, 2025)
Background. In today's post-industrial society, effective public administration is impossible without the introduction of proper communication. The development of information technology and mass communication has led to changes in the ways and forms of interaction between the government and society in the field of public administration. At this stage of the development of public administration, event management is an effective tool for ensuring the communication strategy. It motivates public administration entities to operate efficiently, implement the principles of transparency and accountability of management processes, and helps to improve the interaction between the authorities and society, which increases the level of public trust in government institutions. A key aspect of the introduction of event management in public administration is the effective interaction between the government and society in terms of identifying the target audience, choosing the best information and communication channels of interaction, using them effectively to achieve the set goals, and adapting the communication strategy to the specifics of public authorities and the needs of the public. These issues have been the subject of research on theoretical and practical aspects of event management in the works of such scholars as O. Ivanenko, A. Petrova, V. Kovalenko, M. Smirnov, I. Honcharuk, L. Zakharchenko, V. Zhezhukha, and others. Methods. To obtain the scientific results of the research, the methods of comparative analysis and synthesis were used to identify trends in the introduction of event management for effective interaction between government and society in public administration. The method of content analysis was also used to assess the level of citizens' satisfaction with participation in events, and the effectiveness of interaction between the government and the public to improve the communication strategy. Results. The research of event management as an effective tool for ensuring the communication strategy is an important factor in determining the challenges faced by managers in the process of its implementation in the field of public administration, in particular, the following: lack of human resources, various types of resources (financial, economic, technological, etc.); difficulties in organising effective communication technologies and insufficient level of staff training. Therefore, it is advisable to overcome these obstacles by introducing event management, including the search for additional sources of funding, professional training of staff and improvement of the communication strategy in public administration. Attention is focused on the role of partnership and cooperation between public authorities, NGOs, the private sector and other stakeholders in the implementation of event management. Only through joint efforts can we ensure the completeness and effectiveness of public administration, as well as achieve common goals and the development of society as a whole, and improve the image and reputation of public authorities. Conclusions. In Ukraine, the authorities are focused on establishing a positive dialogue with the public, which would help to strengthen public confidence in the government and support by the population, which is an important element of stable public administration. However, in this direction, there is a need to improve the interaction between the government and society, the implementation of the principles of democracy, and the stability of public policy. The article uses the methods of comparative analysis and content analysis to evaluate the effectiveness of event management in increasing the level of interaction between the authorities and the public. The received results indicate the need to improve personnel support and search for additional resources for the successful implementation of communication strategies. The conclusions of the article can be used to adapt communication strategies in the public sector. Therefore, it is recommended to use event management as an effective tool for ensuring a communication strategy in public administration to actively respond to the changing needs and requirements of the public, which will increase public confidence in the activities of public authorities, mutual understanding between the government and citizens, and increase the overall level of public satisfaction with the quality of public services.

Вступ. Наголошено, що в сучасному постіндустріальному суспільстві ефективне публічне управління неможливе без запровадження належної комунікації. Окреслено, що розвиток інформаційних технологій і засобів масової комунікації спричинив зміни у способах та формах взаємодії влади та суспільства у сфері публічного управління. Зазначено, що на цьому етапі розвитку публічного управління дієвим інструментом забезпечення стратегії комунікацій виступає івент-менеджмент. Це мотивує суб'єктів публічного управління до ефективної діяльності державних установ та організацій, реалізації принципів прозорості, підзвітності управлінських процесів, сприяє покращенню взаємодії органів влади із суспільством, що підвищує рівень довіри громадян до державних інституцій. Розкрито, що ключовим аспектом запровадження івент-менеджменту в публічному управлінні є ефективна взаємодія влади та суспільства щодо визначення цільової аудиторії, вибору оптимальних інформаційно-комунікаційних каналів взаємодії, ефективне використання їх для досягнення поставлених цілей, адаптації стратегії комунікацій до специфіки публічних органів влади та потреб громадськості. Ці питання стали предметом дослідження теоретичних та практичних аспектів івент-менеджменту у працях таких учених, як: О. Іваненко, А. Петрова, В. Коваленко, М. Смирнов, І. Гончарук, Л. Захарченко, В. Жешуха та інших. Методи. Для отримання наукових результатів дослідження використано методи порівняльного аналізу та синтезу з метою виявлення тенденцій запровадження івент-менеджменту задля ефективної взаємодії влади та суспільства в публічному управлінні. Також застосовано метод контент-аналізу для оцінювання рівня задоволеності громадян ефективністю взаємодії влади та громадськості щодо поліпшення стратегії комунікацій. Результати. Обґрунтовано, що дослідження івент-менеджменту як дієвого інструменту забезпечення стратегії комунікацій є важливим чинником у визначенні викликів, з якими стикаються управлінці у процесі його впровадження у сферу публічного управління. Це, зокрема, такі виклики, як дефіцит людського капіталу, різних видів ресурсів (фінансово-економічних, технологічних тощо), складнощі в організації ефективних комунікативних технологій та недостатній рівень підготовки персоналу. Тому доцільно подолати ці перешкоди шляхом запровадження івент-менеджменту, включаючи пошук додаткових джерел фінансування, професійне навчання персоналу та вдосконалення стратегії комунікацій у публічному управлінні. Акцентовано увагу на ролі партнерства та співпраці між органами влади, громадськими організаціями, приватним сектором та іншими зацікавленими сторонами в запровадженні івент-менеджменту. Лише завдяки спільним зусиллям можна забезпечити повноту та ефективність публічного управління, а також досягти спільних цілей та розвитку суспільства загалом, покращити імідж та репутацію органів публічної влади. Висновки. Підкреслено, що в Україні владою акцентовано увагу на налагодженні позитивного діалогу з громадськістю, що сприяло би зміцненню довіри громадян до влади та підтримці її з боку населення, адже це є важливим елементом стабільного публічного управління. Однак існує потреба в удосконаленні взаємодії влади та суспільства, реалізації принципів демократії, стабільності публічної політики. Тому рекомендовано застосовувати івент-менеджмент як дієвий інструмент забезпечення стратегії комунікацій у публічному управлінні задля активного реагування на зміни потреб та вимог громадськості, що сприятиме зростанню довіри громадськості до діяльності публічних органів, взаєморозумінню між урядом та громадянами та підвищенню загального рівня задоволеності громадськості якістю публічних послуг.
ІВЕНТ-МЕНЕДЖМЕНТ ЯК ДІЄВИЙ ІНСТРУМЕНТ ЗАБЕЗПЕЧЕННЯ СТРАТЕГІЇ КОМУНІКАЦІЙ В ПУБЛІЧНОМУ УПРАВЛІННІ
Keywords: public administration; event management; value; instrumental approach; communication management; communication strategies; public; management processes; authorities; positive image; reputation; публічне управління; івент-менеджмент; ціннісність; інструментальний підхід; комунікативний менеджмент; стратегії комунікацій; громадськість; процеси управління; органи влади; позитивний імідж; репутація